2000
DOI: 10.1161/01.str.31.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ganaxolone in a Rodent Model of Cerebral Hematoma

Abstract: Background and Purpose-Therapy with ␥-aminobutyric acid (GABA) agonists appears to improve outcome after experimental hematoma but with unacceptable side effects. We looked to synthetic GABA agonists, or positive GABA modulators, widely developed as anticonvulsants and anxiolytics, to find compounds that may be effective. Ganaxolone is a synthetic neuroactive steroid that positively modulates GABA. We sought to determine whether ganaxolone was beneficial using a model of intracerebral hematoma. Methods-We ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We excluded 10 studies because ICH was not induced using collagenase or autologous blood injection,16–18 outcome data could not be extracted or obtained,19 variance values of zero precluded meta‐analysis,20, 21 or interventions were administered before the induction of ICH22–25 (although we included 3 of these studies in a post hoc sensitivity analysis24–26). After corresponding authors clarified the data in 2 studies,27, 28 we included 88 studies reporting 151 different treatment comparisons (87 of which had sham groups) that described the effects of nonsurgical interventions on neurobehavioral outcome in 2,616 treated or control rodents with ICH (Supporting Information Table 1) 26–113…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 10 studies because ICH was not induced using collagenase or autologous blood injection,16–18 outcome data could not be extracted or obtained,19 variance values of zero precluded meta‐analysis,20, 21 or interventions were administered before the induction of ICH22–25 (although we included 3 of these studies in a post hoc sensitivity analysis24–26). After corresponding authors clarified the data in 2 studies,27, 28 we included 88 studies reporting 151 different treatment comparisons (87 of which had sham groups) that described the effects of nonsurgical interventions on neurobehavioral outcome in 2,616 treated or control rodents with ICH (Supporting Information Table 1) 26–113…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a large number of genes related to potassium channels were downregulated, and if this downregulation were to act like mutations of potassium channel genes, the net result would likely be an increase in brain excitability (Elger, 2005) and presumably an increase in the risk for seizures. It is notable that several studies from Lyden and colleagues have shown that GABA agonists improve outcomes after experimental ICH (Lyden et al, 1997(Lyden et al, , 2000. The combined data suggest that GABA receptor function is decreased after ICH, and GABA receptor activation could be of benefit after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, more neurosteroids have been identified, including PREG and PREG sulfate, PROG and allopregnanolone, deoxycorticosterone, and tetrahydro deoxycorticosterone (THDOC) (Ratner et al, 2019). Although these steroids are supposed to play important pharmacological and physiological roles in the nervous system, some researchers have also studied synthetic neurosteroid analogs, such as alphaxolone (Barker et al, 1987; Granados et al, 2012; Harrison & Simmonds, 1984), ganaxolone (Lyden et al, 2000; Reddy, 2002), and minaxolone (Gourlay et al, 1980; Mitchell et al, 2007; Weir et al, 2004), and the potential therapeutic effects of these drugs on epilepsy and other brain diseases have aroused great interest (Reddy, 2010).…”
Section: Overview Of Neurosteroidsmentioning
confidence: 99%